Pengaruh Intellectual Capital dan Corporate Governance Terhadap Kinerja Bank di Indonesia - Baihaqi, Jadzil (IAIN Surakarta, 2019)
This study examines the impact of intellectual capital and corporate governance mechanism on banks’ performance both directly and also moderated effect. We used banks that were listed in Indonesia Stock Exchange. The bank’s performance was measured by risk-based bank rating while intellectual capital was measured by coefficient of VAIC (Pulic, 1998). The corporate governance mechanism was measured based on the size of boards of directors, composition of independent director, CEO remuneration, managerial ownership, the effectiveness of audit committee and ownership concentration. The result of the study shows that banks’ performance was positively influenced by intellectual capital. However, corporate governance mechanism did not influence the banks’ performance, while moderation effect of corporate governance mechanism on the relationship between intellectual capital and banks’ performance was not confirmed. Keywords: Banks’ Performance; Risk Based Bank Rating; Intellectual Capital; Corporate Governance JEL Classification code: C12, G21, G34, M41